Inspired and inspiring – Maria Montessori, the woman who revolutionized the world of education for children with learning disabilities - Romanowska-Jonio, Sylwia (Difficult situation in biographies: Volume 9, 2025)
Inspiration plays a key role in various areas of life, supporting creativity, motivation, and personal development. It is a process that can enable individuals to achieve their goals, while simultaneously serving as a source of motivation and a model of conduct in different aspects of functioning. In pedagogy, Maria Montessori serves as an example of someone who drew inspiration from the work of others, creating an innovative method initially dedicated to the Children with disabilities. In the 20th century, she established institutions where the methods became a source of inspiration for contemporary approaches in education and upbringing. To deepen the analysis of the topic, original quantitative research was conducted, aimed at understanding the role of inspiration in human life. A diagnostic survey method was used, employing a questionnaire technique, and the tool utilized was an online survey questionnaire.